Mechanical properties improvement of Sand-Based cemented backfill body by adding glass fibers of different lengths and ratios. (19th April 2021) - Zhou, Nan; Du, Erbao; Zhang, Jixiong; Zhu, Cunli; Zhou, Huaqiang
Abstract: Cemented paste backfill (CPB) mining provides a better surface deformation control and waste utilization ability on the ground surface than the conventional mining techniques. However, the overlying rock strata's dislocation produces a shear force or tensile force in the sand-based cemented backfill (SCB). SCB is very likely to undergo breaking and instability, and its bearing capacity is deteriorated. So the improvement of mechanical properties of cemented backfill body by incorporating glass fibers (GF) has become the current trend in global cemented backfill coal mining. This paper presents the experimental investigation of the effect of adding GF with three different lengths (3, 6, and 15 mm) and percent ratios (0.5, 1.0, and 1.5%) to sand-based cemented backfill body (SCB) on the mechanical properties and microstructure of the obtained GF-SCB. The results show that as the GF length and ratio increase, the average peak stress of the SCB firstly rises and then drops. The GF length of 6 mm and the percent ratio of 1.0% are found to ensure the best mechanical properties of the GF-SCB filler. As compared to SCB without glass fibers, the GF-SCB's compressive, tensile, and shear strength values are increased by 23.7, 181.2 and 59.7%, respectively. A scanning electron microscopy examination of GF-SCB filler with different GF lengths and ratios is performed, and the microstructure effect on the filler's mechanical properties is analyzed. These findings reveal the reinforcement mechanism and provide theoretical substantiation of the GF-based improvement of SCB mechanical properties.